MENINGKATKAN HASIL BELAJAR PPKn TEMA 2 PERISTIWA DALAM KEHIDUPAN DENGAN METODE EXAMPLE NON EXAMPLE (ENE) - puspo winarti (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Abstract ______________________________________________________________The indicators of Civic Education on the Second Theme are limited, then the students have lack on mastering the subject about teamwork in all environments and have low on learning outcomes. So, the purposes of this research are to describe the Civic Education learning on the Second Theme, the Events in this Life and to analyze the enhancement of the students learning outcomes. This Classroom Action Research (CAR) is going on the Fifth Class of Waru 3 General Elementary School on the early period on the First Semester of 2018/2019 Academic Year. The subjects are 21 students (10 boys and 11 girls). Techniques of collecting data are nontest and test. Tools of collecting data are observation sheet, multiple choice test and documentation. Technique of analyzing data is comparative-descriptive. The results are learning by observation and discussion also analyzes the pictures in the small group and learning outcomes enhanced to satisfying category.Learning Outcomes, Civic Education, Events, Example Non Example (ENE) Method